Peran Identitas Agama Terhadap Niat Menggunakan Kosmetik Halal : Perluasan Theory of Planned Behavior - Anton Priyo Nugroho; Dzulfikar Izzat; Wuri Suhasti (Universitas Ahmad Dahlan, 2019)
Market share of halal cosmetics in Indonesia increased all of the time. It was not surprising, as a country with the biggest Moslem population in the world, the need of halal cosmetics is a must. Had it trued that the consumption of halal cosmeticsÂ driven by religion (Islam) as a social identity or by other factors. This study tried to find the role of religion as consumerâ€™s social identity with extended theory planned behavior. This study used purposived sampling technics among 100 collage students in Yogyakarta and analyzed with partial Least Square (PLS)s-SEM used smartPLS software. This research found that religion identity was not influenced toward intention to use cosmetics halal. The other variables, attitude, subjective norm and perceived behavior control have a positive and significant influenced toward intention to use halal cosmetics.